CXCL13 Promotes Proliferation of Mesangial Cells by Combination with CXCR5 in SLE - Zhanyun Da; Liuxia Li; Jin Zhu; Zhifeng Gu; Bo You; Ying Shan; Si Shi (Journal of Immunology Research)
As a CXC subtype member of the chemokine superfamily, CXCL13 is considered to be involved in systemic lupus erythematosus (SLE), especially in lupus nephritis (LN). To determine the effect of CXCL13 on SLE and explore the potential mechanisms, we tested serum concentrations of CXCL13 in patients and healthy individuals and found that CXCL13 expression was high in SLE patients especially in LN patients. When we treated human renal mesangial cells (HRMCs) in vitro with recombinant human CXCL13, the cell proliferation was accelerated, which was tested by Cell Counting Kit-8 assay and flow cytometry. Western blot and immunofluorescence assay revealed that CXCL13 would lead to phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2). However, the effect was weakened after the silence of CXCR5. The results of our study elaborated that high expression of CXCL13 could be involved in the pathogenesis of LN.